2013
DOI: 10.1097/mpg.0b013e31829ef82c
|View full text |Cite
|
Sign up to set email alerts
|

Health‐Related Quality of Life in Children With Autoimmune Liver Disease

Abstract: First study to date shows that AILD in children significantly affects HRQOL, especially with frequent liver disease-related symptoms, even in early stages of disease. Findings need to be validated in larger, multicenter studies and will help practitioners understand their patients better and optimize care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 47 publications
0
27
0
2
Order By: Relevance
“…A similar study of HRQoL in 114 treatment naive children with chronic hepatitis C virus demonstrated that, relative to normative data, caregivers were more likely to believe their child’s health was poor, reported higher concern about their child’s health status, and these perceptions limited family activities (26). In studies of children with non-alcoholic fatty liver disease (27) and autoimmune hepatitis (28), decreases in caregivers’ quality of life were found, although use of different HRQoL instruments makes direct comparison difficult. Information on HRQoL in children with chronic HBV is limited.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study of HRQoL in 114 treatment naive children with chronic hepatitis C virus demonstrated that, relative to normative data, caregivers were more likely to believe their child’s health was poor, reported higher concern about their child’s health status, and these perceptions limited family activities (26). In studies of children with non-alcoholic fatty liver disease (27) and autoimmune hepatitis (28), decreases in caregivers’ quality of life were found, although use of different HRQoL instruments makes direct comparison difficult. Information on HRQoL in children with chronic HBV is limited.…”
Section: Discussionmentioning
confidence: 99%
“…(312,314) Low scores on health-related quality of life assessments have been strongly associated with glucocorticoid use. (319)(320)(321)(322) Pretreatment psychological disturbances, especially depression, may be intensified during glucocorticoid treatment. (321) The combined effects of depression, anxiety, and glucocorticoidrelated emotional lability may impact on treatment outcome.…”
Section: Pretreatment Counselingmentioning
confidence: 99%
“…The single study of quality of life in children in autoimmune liver disease showed worse scores than healthy controls across most domains and worse scores than diabetes, liver transplantation, obesity, and rheumatological diseases, with only asthma having lower scores. Parents often feel that their children are doing worse than the children themselves think .…”
Section: Pathogenesismentioning
confidence: 95%
“…The single study of quality of life in children in autoimmune liver disease showed worse scores than healthy controls across most domains and worse scores than diabetes, liver transplantation, obesity, and rheumatological diseases, with only asthma having lower scores. Parents often feel that their children are doing worse than the children themselves think . It is particularly difficult to enable self‐assessment in young children and the currently available tools are culture specific and of varying complexities (Child Health Questionnaire [CHQ], EuroQoL, Beck Youth Inventory [BYI‐2], Paeds‐QL4 including specific transplant module) .…”
Section: Pathogenesismentioning
confidence: 95%